The basic parameters and principles of the strategic control of corporate associations (Путеводитель предпринимателя)
The article deals with the elements of a systematic approach to strategic control of the organization, involving the production of regulations, structure, factors and principles for the implementation of the strategic functions of control in corporate associations.